Shaped by leaky ER: Homeostatic Ca2+ fluxes - Schulte, Annemarie; Blum, Robert (Frontiers in Physiology, 2022)
At any moment in time, cells coordinate and balance their calcium ion (Ca2+) fluxes. The term ‘Ca2+ homeostasis’ suggests that balancing resting Ca2+ levels is a rather static process. However, direct ER Ca2+ imaging shows that resting Ca2+ levels are maintained by surprisingly dynamic Ca2+ fluxes between the ER Ca2+ store, the cytosol, and the extracellular space. The data show that the ER Ca2+ leak, continuously fed by the high-energy consuming SERCA, is a fundamental driver of resting Ca2+ dynamics. Based on simplistic Ca2+ toolkit models, we discuss how the ER Ca2+ leak could contribute to evolutionarily conserved Ca2+ phenomena such as Ca2+ entry, ER Ca2+ release, and Ca2+ oscillations.